Carbapenemase among Clinical Bacterial Isolates in Nepal - Devkota, Surya Prasad; Paudel, Ashmita; Bhatta, Dharm Raj; Gurung, Krishna (Journal of Nepal Health Research Council, 2020)
Gram-negative isolates producing carbapenemase enzymes is a great public health problem in developing countries and their control is challenging task due to the involvement of multiple factors including the practice of self-medication, use of antibiotics on animal farms, poor hospital hygiene, etc. During this study, we searched various databases for relevant publication on carbapenemase-producing isolates in Nepal. Various classes of carbapenemases had been reported in Nepal. Most frequent was the New Delhi Metallo beta lactamase with many variants where NDM-1 was most prevalent. Similarly, Oxacillinase and Klebsiella pneumoniae carbapenemase producers were also prevalent in Nepal. While other carbapenemases like VIM, IPM, and DIM also detected. The isolates producing carbapenemases were extremely drug-resistant as they also co-produced various other carbapenemases, beta-lactamases, 16S rRNA methylase. Most isolates were resistant to many members of carbapenem, cephalosporin, quinolone, penicillin, aminoglycoside group of antibiotics. Such isolates had very few treatment options as only last line drugs like colistin, fosfomycin, and tigecycline was effective against most of these isolates. Carbapenemase production by almost all major human pathogens including E. coli, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter. Citrobacter, Proteus, Providencia is a matter of concern because some of these enzymes are located on plasmids and pose rapid dissemination among various gram-negative pathogens. Timely surveillance for carbapenemase producers throughout the nation, their proper treatment, and proper hospital hygiene to prevent nosocomial infections by carbapenemase producers, controlled use of carbapenems, educating health care workers, students and the general public about the adverse effects of antimicrobial resistance is imminent.